SHRINKAGE BEHAVIOR OF STEEL FIBER REINFORCED CONCRETE ON SANDWICH LAYER CONCRETE - Al Mahdi Jibril, Ramadhan; Purwana, Yusep Muslih (Jurnal Teknik Sipil, 2014)
AbstractShrinkage of concrete causes a serious problem in concrete. If concrete is restrained from shrinking, tensile stresses develop and it may exceed the tensile strength of concrete which causes the concrete cracks. One possible method to control or reduce the adverse effects of cracking due to shrinkage in concrete structures is the addition of fiber in the concrete. Steel fiber can improve structural strength, ductility, reduce crack widths and control the crack. In sandwich layer where its material comprises of steel fiber reinforced concrete and some other by plain concrete. The shrinkage behavior has been considerably different compared to fiber reinforced concrete and plain concrete. Therefore this study investigates the behavioral of shrinkage on the steel fiber reinforced concrete on sandwich layer concept.The test specimens were made by steel fiber dosages of 10kg/m3, 30kg/m3, 50kg/m3, 80kg/m3 and 100kg/m3 and some others for sandwich layer specimen with similar fiber dosages combined with plain concrete. The specimen form was cylinder 5 cm in diameter and 27 cm in high for drying shrinkage test. All samples were placed in open air on ambient temperature environment. The shrinkage was recorded on 1 day to 56 days. The shrinkage prediction for three year or 1000 days was also calculated. Both recorded and predicted shrinkage were then compared..The test result showed that plain concrete experienced the highest drying shrinkage and the addition of steel fiber reduced the drying shrinkage that occurred at concrete. The greater amount of fiber contained in the concrete, the lower occurrence of drying shrinkage. The shrinkage on sandwich samples recorded moderate compared to plain concrete, however this shrinkage is higher compared to samples of fully fiber reinforced concrete at the same fiber dosage. The three group of samples; steel fiber reinforced concrete, sandwich concrete and plain concrete showed the same trend of shrinkage curves following the time of hydration. The presence of steel fiber in concrete can effectively hinder drying shrinkage and affected the crack that can reduce and control the shrinkage of concrete. Keyword: Shrinkage behavior, shrinkage prediction, SFRC, sandwich concrete, plain concrete, steel fiber..